Detection of oral Entamoeba Gingivalis and Trichomonas Tenax in adult quilombola population with periodontal disease = Detección de Entamoeba Gingivalis oral y Trichomonas Tenax en población de quilombola adulta con enfermedad periodontal - Araújo Rosa, Jamille Alves
The objective was to analyze the periodontal condition severity and the occurrence of pathogenic microorganisms in the oral cavity of an adult population of an Afrodescent Community of northeastern Brazil. This is an observational and cross-sectional study performed through an oral clinical examination, using a standardized clinical record. For the subjects with periodontal disease, the bacterial biofilm was collected in a Petri dish containing 0.9% physiological solution to detect the presence of microorganisms Entamoeba gingivalis and Trichomonas tenax, and later observed under an optical microscope. Statistical analysis was performed by calculating the prevalence of periodontal disease and the frequency of the protozoa in the bacterial biofilm. Statistical significance of the relationships researched was verified by Fisher's exact test. It was evaluated 29 subjects pertaining to the Quilombola Patioba community, aged 35 to 44 years. The results showed that among the adults of the community, there was a high prevalence of periodontal disease (75.86%), being higher in the 1st and 6th sextants of the Community Periodontal Index (CPI). E. gingivalispositivity occurred in most sextants affected by gingivitis, while in the condition of periodontitis, this microorganism was not present in the 3rd, 4th and 6th sextants. In all sextants affected by periodontal disease, T. Tenax was observed when associated with gingivitis. It is worth mentioning the begging of the elaboration of health policies, social and professional commitment that foster a greater promotion of oral health and quality of life for the quilombolas of northeastern Brazil.